The relationship between residual sphincter damage after primary repair, faecal incontinence, and anal sphincter function in primiparous women with an obstetric anal sphincter injury. Issue 1 (2nd November 2018) - Patton, Vicki; Kumar, Swetha; Parkin, Katrina; Karantanis, Emmanuel; Dinning, Phil
Abstract : Background and Aims: Anal sphincter injury has been identified as a primary cause of post‐partum fecal incontinence in women with obstetric anal sphincter injury. However, women without obstetric anal sphincter injury may also develop fecal incontinence. The aim is to determine the relationship between fecal incontinence severity; and i) residual anal sphincter injury, quantified by the Starck score, and ii) anal sphincter tone. Methods: Consecutive case series of prospectively collected data set in a Pelvic Floor Unit within a tertiary teaching hospital in Australia. Population 181 primiparous women with Sultan classification Grade 3 and 4 sphincter injuries. Main outcome measures: Sultan classification, anal manometry, pudendal nerve terminal motor latency, St Mark's fecal incontinence score, and Starck ultrasound score. Results: 45% of women reported some degree of fecal incontinence. One third of women with normal external sphincter tone were incontinent. Those with higher Starck score had higher St Mark's scores. A higher Sultan classification correlated with more severe incontinence regardless if the repair was complete. Forceps delivery had a twofold risk of incontinence when compared to non‐forceps delivery. Conclusion: The importance of an effective anal sphincter repair is confirmed. However, overall there is no direct relationship between residual sphincter damage, anal sphincter tone, and fecal incontinence severity. These data indicate that anal sphincter integrity alone is not the sole mechanism for maintaining fecal continence. Rectal and colonic motor function may also play a role and investigation into these components may provide greater insight into the effect of vaginal delivery upon fecal continence mechanisms